An unusual stent migration after endoscopic ultrasound-guided choledochoduodenostomy - Aditya Kale; Sridhar Sundaram; Manish Dodmani (Society of Gastrointestinal Intervention, 2022)
Summary of event: Endoscopic ultrasound-guided choledochoduodenostomy (EUS-CD) with the placement of a fully covered self-expandable metal stent (SEMS) is an alternative method to percutaneous transhepatic biliary drainage in cases of failed endoscopic retrograde cholangiopancreatography (ERCP) for malignant distal biliary obstruction. We report the case of a 64-year-old female who underwent EUS-CD with placement of a fully covered SEMS for obstructive jaundice due to distal bile duct obstruction by a pancreatic head mass and failed ERCP. Five months after the procedure, she presented with spontaneous expulsion of the stent in vomitus. She did not have bile leak and jaundice due to the formation of an epithelialized fistulous tract between the bile duct and duodenum (choledocho-duodenal fistula). Teaching point: Delayed distal migration of a fully covered SEMS after EUS-CD can occur. The formation of an epithelialized choledochoduodenal fistula prevented the occurrence of bile leak, pneumoperitoneum and perforation. Re-stenting through the same tract is possible. Stents with antimigration flanges or lumen-apposing metal stents may prevent migration.